1992
DOI: 10.1007/bf01766463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium deprivation on contraction and charge movement in frog skeletal muscle fibres

Abstract: Measurements of isometric tension were performed in single twitch skeletal muscle fibres and the effect of extracellular Na+ removal on contraction was investigated. Na+ withdrawal brought about an increase in the amplitude of K+ contractures and their time course became faster. The potentiation of K+ contractures depended strongly on extracellular Ca2+ and developed slowly following an exponential time course with a time constant of approximately 8 min. Removal of extracellular Na+ greatly increased the ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…This potential mechanism is supported by a number of electrophysiological studies that demonstrate that TRPCs allow permeation of Na ϩ as well as Ca 2ϩ (42,43 (44,45). The absence of muscle activation in MHN muscles is in agreement with previous studies where the effect of extracellular Na ϩ withdrawal had been studied in diverse muscle preparations (15,46,47).…”
Section: Discussionsupporting
confidence: 86%
“…This potential mechanism is supported by a number of electrophysiological studies that demonstrate that TRPCs allow permeation of Na ϩ as well as Ca 2ϩ (42,43 (44,45). The absence of muscle activation in MHN muscles is in agreement with previous studies where the effect of extracellular Na ϩ withdrawal had been studied in diverse muscle preparations (15,46,47).…”
Section: Discussionsupporting
confidence: 86%
“…Parallel measurement of intracellular [Ca 2ϩ ] using fluo 3 as the Ca 2ϩ indicator revealed that, when the fiber was exposed to zero external [Na ϩ ], only a small increase in cytoplasmic [Ca 2ϩ ] that was partially reversed on reperfusing the fiber with Ringer was observed. This limited increase in [Ca 2ϩ ] was not enough to produce contractures, in agreement with previous reports (13,26). However, fibers became somewhat swollen when exposed to external solutions without Na ϩ .…”
Section: Fiber Experimentssupporting
confidence: 91%
“…In agreement with this rather low Ca 2ϩ affinity, to detect Na ϩ -dependent Ca 2ϩ efflux in amphibian single fibers, it is necessary to increase the intracellular Ca 2ϩ concentration ([Ca 2ϩ ]) well above its resting level (22). The reverse mode of the exchanger may cause the enhancement of contraction that takes place after external Na ϩ withdrawal in phasic (8,13,17,26) or tonic (24) amphibian skeletal muscle fibers.…”
mentioning
confidence: 99%
“…In fact, although our depolarizing solutions contained a low concentration of sodium ions and therefore a decreased efflux of Ca 2+ through the Na + /Ca 2+ exchanger might be expected, the exchanger appears to play a minor role in this process as compared to its role in cardiac muscle and tonic fibers [5]. Furthermore, charge movement is not affected by deprivation of extracellular sodium ions [16]. Finally, we did not observe changes in fluorescence that might indicate an elevation in resting myoplasmic Ca 2+ by protracted depolarization.…”
Section: Mechanism Of Down-regulationmentioning
confidence: 97%